Red cell distribution width and risk of venous thromboembolism - Ellingsen, Trygve Sølberg (UiT The Arctic University of Norway, 2018)
Paper I of the thesis is not available in Munin. Ellingsen, T.S., Lappegård, J., Skjelbakken, T., Brækkan, S.K. & Hansen, J.B. (2015). Red cell distribution width is associated with incident venous thromboembolism (VTE) and case-fatality after VTE in a general population. The manuscript version of this paper is available in Munin at http://hdl.handle.net/10037/7364 . Venous thromboembolism (VTE) is a collective term for deep vein thrombosis and pulmonary embolism. VTE is the third most common cardiovascular disease, causing significant morbidity and mortality. The incidence of VTE has been stable or slightly increasing during the last decades, affecting 1-2 per 1000 individuals each year. Up to half of all VTE patients have no obvious cause of the disease. Thus, identifying novel biomarkers and unraveling underlying disease mechanisms might help diminish the health burden of VTE. Red cell distribution width (RDW) is a measure of the variability of size of the circulating red blood cells. RDW increase due to various conditions that alter the bone marrow’s production of red blood cells, such as iron deficiency. Recent years, RDW has been associated with risk of several diseases. The first aim of this thesis was to investigate whether RDW is associated with future risk of VTE and mortality among VTE patients. Secondly, we aimed to investigate whether the association could be explained by underlying iron deficiency or intermediate development of other diseases. All papers in this thesis use data from the Tromsø Study, a large population-based cohort study. Our study populations were recruited from the fourth survey. For paper I, subjects were followed from date of inclusion in 1994/95 through January 1, 2012. In paper III and IV, study participants were followed from date of inclusion through December 31, 2010. Paper II is a nested case-control study with cases and controls selected among participants in Tromsø 4. Validated events of VTE, cancer, myocardial infarction (MI) and stroke were registered throughout ...